2023
DOI: 10.1039/d2nr06710b
|View full text |Cite
|
Sign up to set email alerts
|

Iodide/triiodide redox shuttle-based additives for high-performance perovskite solar cells by simultaneously passivating the cation and anion defects

Abstract: Halide perovskite solar cells (PSCs) have received remarkably increasing interests due to the facile fabrication procedures, cost-effective raw materials and skyrocketed power conversion efficiencies (PCEs) during the past 10 years....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…More recently, other works suggested that introducing I 3 − during 3D perovskite formation helps prevent/regenerate point defects, like metallic lead. 61,62 This indicates that the spontaneous iodine oxidation when using PbO 2 as precursor naturally provides the right chemical environment to produce high quality BAPI.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, other works suggested that introducing I 3 − during 3D perovskite formation helps prevent/regenerate point defects, like metallic lead. 61,62 This indicates that the spontaneous iodine oxidation when using PbO 2 as precursor naturally provides the right chemical environment to produce high quality BAPI.…”
Section: Discussionmentioning
confidence: 99%
“…The general utility of the I – /I 3 – redox couple is relatively commonplace, as seen with its continuing use in the electrolyte of dye-sensitized solar cells (DSCs), while the redox chemistry of iodine has recently been explored for use in several types of rechargeable batteries . In addition, organic triiodides have been used as intermediates in the synthesis of MAPbI 3 perovskite films or as a defect scavenger in lead-based perovskite solar cells . In a similar fashion, iodide has been shown to react with oxygen in aqueous solutions , to form I 2 , which quickly forms I 3 – in the presence of additional I – (eq , k = 5.6 × 10 9 L mol –1 s –1 , K eq = 710 L mol –1 in H 2 O at ambient temperatures).…”
Section: Methodsmentioning
confidence: 99%
“…Besides the development of multifunctional organic additives for CBI-based PSCs, inorganic potassium iodide (KI) was demonstrated as a promising defect-passivating additive in organic-inorganic perovskites utilizing surplus iodide species of KI additive to suppress the halide vacancies of perovskite films. [137][138][139][140] As for the CBI-based PSCs, Hamukwaya et al incorporated KI as functional additives to improve the crystallinity and grain sizes as well as to stabilize the crystal structures of Cs 3 Bi 2 I 9 films. [66] Consequently, the carbon electrode-based cell with optimized KI amount (2 vol%) exhibited a much superior PCE of 2.81% (Figure 7e) to that of the control device (0.28%) due to optimized surface morphology (Figure 7f ), increased diffusion potential, and suppressed interfacial energy barrier.…”
Section: Additive Engineeringmentioning
confidence: 99%